1985
DOI: 10.1128/jcm.21.4.643-644.1985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two immunofluorescence assays with monoclonal antibodies for typing of herpes simplex virus

Abstract: An indirect immunofluorescence assay and a direct immunofluorescence assay were evaluated for typing clinical isolates of herpes simplex virus (HSV). The indirect immunofluorescence assay (Electro-Nucleonics, Inc.) correctly identified 16 HSV type 2 (HSV-2) isolates, but failed to identify 4 of 14 HSV-1 isolates because of background fluorescence and instability of reagents. Forty-nine HSV-1 isolates were correctly typed by direct immunofluorescence assay (Kallestad Laboratories, Inc.), but 1 of 39 HSV-2 isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Consequently, it would be unrealistic to suggest that monoclonal antibodies prepared against a single epitope would react with all isolates. The specificity of monoclonal antibodies and the antigenic complexity of HSV strains may therefore explain, in part, discordant typing results reported in this and other studies (4,9). It is interesting that for the 108 positive specimens tested, ENI type-common and HSV-2 typespecific monoclonal antibodies displayed a sensitivity and specificity of 100%.…”
Section: Resultssupporting
confidence: 43%
See 2 more Smart Citations
“…Consequently, it would be unrealistic to suggest that monoclonal antibodies prepared against a single epitope would react with all isolates. The specificity of monoclonal antibodies and the antigenic complexity of HSV strains may therefore explain, in part, discordant typing results reported in this and other studies (4,9). It is interesting that for the 108 positive specimens tested, ENI type-common and HSV-2 typespecific monoclonal antibodies displayed a sensitivity and specificity of 100%.…”
Section: Resultssupporting
confidence: 43%
“…Swierkosz and co-workers (9) recently reported that background fluorescence probably obscured the determination of HSV (by the Virgo system) among 4 of 10 HSV-1 confirmed isolates. Their results are difficult to explain, as background fluorescence was not a problem in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience underscores the problem with relying exclusively on MAb-based detection systems in a diagnostic virology laboratory. Viral variants that occasionally fail to react with monoclonal reagents do occur (12).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical virology reagent market continues to have an influx of monoclonal antibody stains from different manufacturers who are capitalizing on the growing number of clinical virology laboratories (1,4,5,7,(10)(11)(12). With an increasing number of small community hospitals and laboratories delving into the area of HSV isolation, the demand for highquality low-cost HSV reagents has grown.…”
mentioning
confidence: 99%